Tingkat Kepuasaan Pengguna Perpustakaan SMK Negeri 17 Samarinda Melalui Pemasangan Poster dan Label Perpustakaan - Cahyaningrum, Gyta Krisdiana; Indriani, Annisa Silviana; Putri, Mahadewi Mahesa; Kania, Nazhwa Astri; Adawiyah, Rabiatul; Riendy; Raki, Visal Surya (Lembaga Dongan Dosen, 2025)
This study aims to analyze the satisfaction of library users of SMK Negeri 17 Samarinda after the implementation of library posters and labels. A survey method was used involving several respondents consisting of 42 students of SMK Negeri 17 Samarinda as the main users of the library. Data were collected through a questionnaire that measured user perceptions of information clarity, ease of access, and comfort of the library environment after the installation of posters and labels. The results showed that 85% of respondents stated that the posters provided information that was clear and easy to understand, and 90% of respondents considered that the labels could help facilitate the search for book collections. Overall, the level of user satisfaction increased from 65% to 90% after the intervention. The conclusion of this study confirms that the installation of posters and labels is an effective strategy to improve user comfort and convenience in utilizing library services. The recommendation is to expand the use of visual media in the library to increase user satisfaction further.